Features and Characteristics of the Jurisdictional Regime of the International Criminal Court - Khamzakhonov Sunnatillo; Gavkherjan Yuldasheva (Periodica Journal, 2022)
The purpose of writing this article is the question of the jurisdictional regime of one of the most important courts in the world - the International Criminal Court, established by the Rome Statute. In view of the emergence of certain debatable issues regarding the jurisdiction of the court to consider cases of commission of crimes within the subject matter jurisdiction of the International Criminal Court
Keywords: principle; court; International; commission